Pergeseran Paradigma Maqasid Al-Syari'ah: Dari Klasik Sampai Kontemporer - Muhammad Lutfi Hakim (Al-Manahij: Jurnal Kajian Hukum Islam, 2016)
Islamic syari'ah was revealed to give benefits to everyone and to avoid them from disadvantages of lives, therefore syari'ah is meant to be suitable and compatible with the development of human beings. This is the basic concept of maqasid al-syari'ah as introduced and explained by the medieval Islamic scholar Imam al-Syațibiin his book al-muwafaqat. However, the concept of maqasid al-syari'ah is experiencing development from time to time and it has become a new paradigm in the contemporary Islamic philosophy. new paradigm of maqasid al-syari'ah is introduced by popularized by Jasser Auda with a systems approach. The development of paradigm of maqasid, from the old to the new maqasid, can be seen from its emphasizing of meaning. The old concept ofmaqasid emphasizes protection of human beings and preservation of benefits, while. the new concept of maqasid emphazies development of human beings and their rights.